Compact holographic optical element-based electronic speckle pattern interferometer for rotation and vibration measurements - Bavigadda, Viswanath (2017)
An out-of-plane sensitive electronic speckle pattern interferometer (ESPI) using holographic optical elements (HOEs) for studying rotations and vibrations is presented. Phase stepping is implemented by modulating the wavelength of the laser diode in a path length imbalanced interferometer. The time average ESPI method is used for vibration measurements. Some factors influencing the measurements accuracy are reported. Some advantages and limitations of the system are discussed.